Determining the daily digestible protein intake for nile tilapia at different growth stages - Castillo, Julian David Alvarado [UNESP]; do Nascimento, Thiago Matias Torres [UNESP]; Mansano, Cleber Fernando Menegasso [UNESP]; Sakomura, Nilva Kazue [UNESP]; da Silva, Edney Pereira [UNESP]; Fernandes, João Batista Kochenborger [UNESP] (Boletim do Instituto de Pesca, 2017)
This study aimed to estimate the utilization efficiency and optimal intake of digestible protein to maximize weight gain and feed conversion in Nile tilapia juveniles at different development stages. Four trials, each lasting 45 days, were performed using sexually inverted Nile tilapia juveniles with an initial average weight of 2.01 g (phase A), 14.26 g (phase B), 59.96 g (phase C), and 149.11 g (phase D). The experimental design was completely randomized with five treatments and four replicates. The levels of digestible protein ranged from 175 to 425 g kg-1 (phase A), 163 to 390 g kg-1 (phase B), 150 to 360 g kg-1 (phase C), and 138 to 330 g kg-1 (phase D). The maximum responses in terms of weight gain were obtained with protein intakes (digestible protein) of 88, 328, 713, and 855 mg fish-1 day-1, respectively, for phases A, B, C, and D. The maximum feed conversion ratio was obtained with protein intakes of 78, 272, 697, and 793 mg fish-1 day-1, respectively, for phases A, B, C, and D. The protein utilization efficiency was 52, 51, 51, and 50% for phases A, B, C, and D, respectively.
Determinação da ingestão diária de proteína digestível para tilápia-do-nilo em diferentes fases de crescimento
Keywords: Feed conversion; Oreochromis niloticus; Protein deposition; Weight gain